2021
DOI: 10.1021/acs.inorgchem.0c03269
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Metal Exchange between a Metalloid Silver Cluster and Silver(I) Thiolate

Abstract: Although a homometallic (isotopic metal) exchange reaction has been reported, the in-depth understanding of the interaction between a metalloid cluster and the homometal (representing the same metal element as the metalloid cluster) thiolate is quite limited, especially at the atomic level. Herein, based on Ag 44 (SR) 30 (where SR represents 4-mercaptobenzoic acid), we report a facile approach for investigating the metalloid cluster−homometal thiolate interaction at the atomic level, i.e., isotopic exchange in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…Isotopic exchange reactions have been widely used to understand dynamics in the structures of proteins and polymers. Similarly, isotopic exchange in NCs also resolved their structural dynamics. , Two Ag 25 (DMBT) 18 – NCs, prepared with isotopically pure 107 Ag and 109 Ag, respectively, reacted to produce isotopically mixed Ag 25 (DMBT) 18 – . The isotopic exchange was similar to the exchanges observed in H 2 O and D 2 O, which revealed that NCs indeed behave as simple molecules.…”
Section: Introductionmentioning
confidence: 78%
“…Isotopic exchange reactions have been widely used to understand dynamics in the structures of proteins and polymers. Similarly, isotopic exchange in NCs also resolved their structural dynamics. , Two Ag 25 (DMBT) 18 – NCs, prepared with isotopically pure 107 Ag and 109 Ag, respectively, reacted to produce isotopically mixed Ag 25 (DMBT) 18 – . The isotopic exchange was similar to the exchanges observed in H 2 O and D 2 O, which revealed that NCs indeed behave as simple molecules.…”
Section: Introductionmentioning
confidence: 78%
“…The previous experimental and theoretical studies indicated that the motif-doped M@Au 24 (SR) 18 (M = Ag, Cd, and Hg) is metastable, and the Ag, Cd, and Hg atoms are located on the surface of the icosahedral core in the final product of metal displacement. In the recent studies of the allotropic displacement reactions of the Ag 29 cluster, Wang et al proposed that metal atoms in the core can be displaced by metal atoms in the shell of metal clusters. Moreover, it was confirmed that the metal diffusion from the ligand shell to the internal metal core is the rate-determining step of metal displacement reaction . Although these experimental studies identified that the metal diffusion from the ligand shell to the core is an important process of metal displacement, the detailed atomic process of this metal diffusion remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was confirmed that the metal diffusion from the ligand shell to the internal metal core is the rate-determining step of metal displacement reaction. 39 Although these experimental studies identified that the metal diffusion from the ligand shell to the core is an important process of metal displacement, the detailed atomic process of this metal diffusion remains unclear. Herein, we report a new intra-cluster metal diffusion mechanism, which proposes that the terminal SR of the newly formed [SR-Au I -SR] species acts as a nucleophilic agent to attack the Au atom on the icosahedron core, leading to the formation of an atomic vacancy on the surface of the Au 13 core (IM4 → IM5) and a long [SR-Au-SR-M-SR-Au-SR-Au-SR] motif on the cluster surface.…”
Section: Resultsmentioning
confidence: 99%
“…45 The free R-DHLA ligand molecules and/or silver−DHLA complex in the solution therefore play a decisive role in the handedness inversion through thermally activated frequent ligand and/or silver−DHLA exchange processes. 52 Recently, a mechanism that does not require the breakage of Au−S bonds was proposed for the rearrangement of gold−thiolate oligomeric staple motifs on the surface of Au 38 core involving a rotational reconstruction of core. 53 However, the surface framework of Ag 29 NC is not simply composed of silver−thiolate oligomeric chains, 46 which may exclude the rotational reconstruction mechanism.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It should be also noted that the purification process to remove the excess R -DHLA ligand resulted in the degradation of Ag NCs on heating . The free R -DHLA ligand molecules and/or silver–DHLA complex in the solution therefore play a decisive role in the handedness inversion through thermally activated frequent ligand and/or silver–DHLA exchange processes . Recently, a mechanism that does not require the breakage of Au–S bonds was proposed for the rearrangement of gold–thiolate oligomeric staple motifs on the surface of Au 38 core involving a rotational reconstruction of core .…”
Section: Resultsmentioning
confidence: 99%